APLIKASI MODEL TREND UNTUK MEMPREDIKSI PRODUKSI KELAPA SAWIT PROVINSI KALIMANTAN SELATAN - Salam, Nur; Lestia, Aprida Siska; Jannah, Noor; Firdaus, Muhammad (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2024)
The plantation sector has a large and extensive reach, one type of plantation crop that is widely cultivated in Indonesia is oil palm. Business in the oil palm plantation sector is also one of the leading potential areas in South Kalimantan Province. One of the provinces producing the most palm oil in Indonesia is South Kalimantan Province. This research is a literature study regarding predictions of palm oil production. The aim of this research is to determine the appropriate prediction model for data on the amount of palm oil (CPO) production in the South Kalimantan Province Region and to explain the results of palm oil predictions in the South Kalimantan Province Region using a trend model. The application of the trend model used in this research takes into account the error value obtained with the smallest MAPE (Mean Absolute Percentage Error). The nature of the data regarding the amount of palm oil production in the South Kalimantan Province Region from 2001 to 2021 tends to continue to increase so that the data can be predicted using trend methods, namely linear, quadratic and exponential. For the prediction results of palm oil production using the best trend model with the smallest MAPE value, namely 16% with the linear trend model: ... The predicted amounts of palm oil production from 2022 to 2027 which tend to continue to increase are: 1.336.359, 1.397.196, 1.458.032, 1.518.869, 1.579.705 and 1.640.542 tons.